Impacts of the COVID-19 pandemic on operational losses - Medina, Fabio Augusto Scalet; Kimura, Herbert (Frontiers in Applied Mathematics and Statistics, 2022)
The main objective of the present study was to determine whether the COVID-19 pandemicimpacted the frequency and severity of financial institutions’ operational losses. We selectedfour types of operational-risk events and, applying linear regression, concluded that thepandemic impacted the severity of operational losses. Regarding the frequency of operationallosses, we observed no statistically significant difference between pre- and postpandemiclosses; however, regarding the severity of losses, we observed an increase in thepostpandemic period for the aggregate data, and when analyzing the types of operational-riskevents individually, we observed that the frequency of some events increased and othersdecreased after the pandemic, requiring a detailed investigation of the reasons for the increaseor decrease in the severity of losses.